Cryo-EM structure of the RC-LH core complex from an early branching photosynthetic prokaryote - Yueyong Xin (Nature Portfolio, 2018)
Filamentous anoxygenic phototrophs (FAPs) are phylogenetically distant from other anoxygenic photosynthetic bacteria. Here the authors present the 4.1 Å cryo-EM structure of the photosynthetic core complex from the FAP Roseiflexus castenholzii and propose a model for energy and electron transfer.